Direct Identification of Surface Bound MoO3 on Single MoS2 Flakes Heated in Dry and Humid Air. Issue 13 (6th June 2021) - Rogala, Maciej; Sokołowski, Stanisław; Ukegbu, Ugonna; Mierzwa, Aneta; Szoszkiewicz, Robert
Abstract: The chemical presence of the MoO x species on single microscopic MoS2 flakes is shown at two conditions, which are of interest for future MoS2 ‐based devices and where their presence is not previously confirmed. First, the case of thick MoS2 flakes oxidatively etched at 350–370 °C in air is treated. Atomic force microscopy (AFM), high resolution X‐ray photoelectron spectroscopy, and X‐ray absorption spectroscopy are combined to unambiguously confirm the chemical presence of the α‐MoO3 species on such samples, mostly in the form of loose particles. Second, it is shown that MoS2 flakes heated at temperatures of only 220 °C display a quite uniform ≈2 nm thick MoO x layer at already 10% relative humidity. The presence of such MoO x oxide layers is confirmed by scratching the sample with AFM tips and performing comparative Kelvin probe force microscopy and Auger photoelectron spectroscopy on scratched‐out and untouched parts of the flakes. Abstract : MoO x species on MoS2 flakes are investigated. For samples oxidatively etched at 350–370 °C in air MoO3 species are detected as particles via atomic force microscopy (AFM), X‐ray photoelectron spectroscopy and X‐ray absorption spectroscopy. For flakes heated at 220 °C at 10% relative humidity, 2 nm thick MoO x layer is observed via AFM and Auger photoelectron spectroscopy.